Asymmetries in the Temporal Variation of the Electron Content During a Solar Eclipse - A. Meza; G. Bosch; M. P. Natali; B. Eylenstein; A. Urutti (Earth and Space Science)
Abstract Solar eclipses offer a unique opportunity to study rapid variations in the Earth's atmosphere. By accurately modeling the timing and magnitude of obscuration caused by the Moon's shadow, we can investigate the eclipse's impact on the behavior of the Earth's ionosphere. Our approach involves deriving the vertical total electron content (VTEC) of the ionosphere using navigation satellite signals. Our previous research, conducted during the 2017 North American eclipse, focused on a limited area. We employed a skewed Gaussian profile to model the temporal variation of the ΔVTEC curve, introducing a new parameter to better characterize the time delay in the ionosphere's response. This study broadens our research to include the East Coast and integrates the Global Ionosphere‐Thermosphere Model (GITM). The skewness parameter reflects the relative durations of ionospheric decay and recovery, where positive values indicate rapid decay coupled with slow recovery and negative values suggest the opposite. Although our ΔVTEC simulation using GITM qualitatively matches observed behaviors, it faces challenges in accurately capturing the maximum drop and recovery phases, particularly in the eastern regions, likely due to insufficient consideration of plasmaspheric refilling, which significantly influences the recovery of the upper ionospheric layers. The path of the eclipse totality delineates a boundary where positive asymmetries are observed to the south while negative asymmetries appear to the north.